2012
DOI: 10.1088/0957-4484/24/1/015702
|View full text |Cite
|
Sign up to set email alerts
|

Imaging layer number and stacking order through formulating Raman fingerprints obtained from hexagonal single crystals of few layer graphene

Abstract: Quantitative mapping of layer number and stacking order for CVD-grown graphene layers is realized by formulating Raman fingerprints obtained on two stepwise stacked graphene single-crystal domains with AB Bernal and turbostratic stacking (with ~30°interlayer rotation), respectively. The integrated peak area ratio of the G band to the Si band, A(G)/A(Si), is proven to be a good fingerprint for layer number determination, while the area ratio of the 2D and G bands, A(2D)/A(G), is shown to differentiate effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 61 publications
8
46
2
Order By: Relevance
“…1a) exhibited a 2D/G peak ratio of 2.2 and a symmetric 2D band with full width half maximum (FWHM) of 30 cm −1 . 2D/G peak ratio measured from 10 Raman spectra from the single layer areas was found to be 2.3 ± 0.3, which confirms the single layer assignment1148. In addition, the intensity of G band is almost proportional to the number of graphene layers49, which confirmed the existence of double layer domain (position 2 in Fig.…”
Section: Resultssupporting
confidence: 68%
“…1a) exhibited a 2D/G peak ratio of 2.2 and a symmetric 2D band with full width half maximum (FWHM) of 30 cm −1 . 2D/G peak ratio measured from 10 Raman spectra from the single layer areas was found to be 2.3 ± 0.3, which confirms the single layer assignment1148. In addition, the intensity of G band is almost proportional to the number of graphene layers49, which confirmed the existence of double layer domain (position 2 in Fig.…”
Section: Resultssupporting
confidence: 68%
“…In particular, the I 2D /I G ratio decreases as the number of graphene layers increases. Peak positions of G and 2D bands, the I 2D /I G ratio and FWHMs of 2D bands of the Raman spectra of three devices that we tested here confirm the formation of multilayer graphene (see Supporting Information, Section S1) . The presence of a weak D‐band with CVD‐assisted grown graphene is expected because the laser spot (∼1 μm) is much larger than the size of a typical graphene domain (20–100 nm).…”
Section: Resultssupporting
confidence: 61%
“…It is observed that the absence of D peak in the pure 3D‐C sample indicates the presence of high quality pristine graphene. The second‐order Raman band (2D band) can be used to estimate the number of layers of CVD‐grown graphene according to its relative intensity with respect to the G band (I 2D /I G ) . The intensity of the G band is about 4 times higher than the intensity of the 2D band (I 2D /I G ≈0.25), indicating multi‐layer graphene.…”
Section: Comparison Between Measured Thermal Conductivity Of the Foammentioning
confidence: 99%